The Influence of Knowledge Management on Human Resource Development of Culinary SMEs in Makassar - Ferdinandus Sampe; Nataniel Papalangi; Uli Urbanus Bubun; Abner Tahendrika; Wihalminus Sombolayuk (www.amertainstitute.com, 2025)
This study aims to investigate the influence of knowledge management practices on the human resources development within culinary Small and Medium Enterprises (SMEs) in Makassar, providing empirical insights into how the strategic acquisition, sharing, and application of knowledge can foster enhanced employee capabilities and organizational resilience. This research explores the specific mechanisms through which knowledge management initiatives, such as formal training programs, informal learning networks, and technological platforms, contribute to the upskilling and reskilling of the workforce in this dynamic sector. Using organizational learning approach, knowledge management and human resource development indicators were developed. Data from this study obtained from questionnaires distributed directly to owner or manager of culinary SMEs in Makassar. Multiple regression was applied to analyze the data. The finding of this research show that knowledge management consists of knowledge development, knowledge sharing/distribution and utilization of knowledge were simultaneously have positive significant influence the development of human resources. The results offer practical insights, including policy recommendations for improving human resource development in culinary SMEs.